2021
DOI: 10.1017/s0022215121000992
|View full text |Cite
|
Sign up to set email alerts
|

Post coronavirus disease mucormycosis: a deadly addition to the pandemic spectrum

Abstract: Objective To study the possible association between invasive fungal sinusitis (mucormycosis) and coronavirus disease. Methods A prospective observational study was conducted at a tertiary care centre over four months, involving all patients with mucormycosis of the paranasal sinuses suffering from or having a history of coronavirus disease infection. Results Twenty-three patients presented with mucormycosis, all had an association with coronavirus disease 2019. The ethm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
389
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(445 citation statements)
references
References 29 publications
25
389
2
1
Order By: Relevance
“…Also, other therapeutic options besides reversal of underlying cause must be implemented as the reversal of these conditions may not be possible while treatment is ongoing for COVID-19. This is especially true due to the need to use high doses of steroids for the treatment of COVID-19 ( Moorthy et al, 2021 ; Sharma et al, 2021 ). In this condition, it is evident that the use of antibiotics and steroids may be dangerous for some patients as they may trigger the onset of these life-threatening fungal infections.…”
Section: Covid-19 and Mucormycosis: A Tangled Relationmentioning
confidence: 99%
“…Also, other therapeutic options besides reversal of underlying cause must be implemented as the reversal of these conditions may not be possible while treatment is ongoing for COVID-19. This is especially true due to the need to use high doses of steroids for the treatment of COVID-19 ( Moorthy et al, 2021 ; Sharma et al, 2021 ). In this condition, it is evident that the use of antibiotics and steroids may be dangerous for some patients as they may trigger the onset of these life-threatening fungal infections.…”
Section: Covid-19 and Mucormycosis: A Tangled Relationmentioning
confidence: 99%
“…The increasing number of recent case series of mucormycosis complicating COVID-19 patients in the United States, 10 – 16 Austria, 17 Brazil, 18 Mexico, 19 Italy, 20 France, 21 Iran, 22 – 24 and India, 25 – 34 raises concerns regarding the misuse of immunosuppressive drugs in patients with COVID-19. Mucormycosis is a neglected mycosis that should be considered in the context of patients with COVID-19, in the same way as COVID-19 associated pulmonary aspergillosis, and it is possibly underreported.…”
mentioning
confidence: 99%
“…Classically, uncontrolled diabetes mellitus, neutropenia, and corticosteroid therapy are known risk factors for mucormycosis. 22 , 37 There is an urgent need to reconsider the careful use of these drugs in patients with severe COVID-19 due to the high prevalence of underlying comorbidities in these patients, 11 – 13 , 25 , 28 – 30 including diabetes mellitus, 13 , 16 , 19 , 26 , 28 – 30 hematological malignancies (i.e. acute myeloid leukemia), 17 end-stage kidney disease, 27 and organ transplant recipients.…”
mentioning
confidence: 99%
“…Severely ill Covid-19 patients can develop fungal infections during the middle and latter stages of their disease [1]. In a recent article, Post coronavirus disease mucormycosis: a deadly addition to the pandemic spectrum, Sharma et al suggested that extensive use of steroids in the management of Covid-19 might facilitate the emergence of the infection mucormycosis by suppressing the immunity [2], a mold infection resulting in high morbidity and mortality rates [3]. The primary route and cause of this opportunistic infection is the inhalation of spores of the species Rhizopus oryzea, abundant in the environment.…”
Section: Introductionmentioning
confidence: 99%